This I Know to be True: Ethnology, Divination and the Processes of Authenticity - Sawden, Kari (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2018)
Working within alternative belief communities, I frequently encounter a tension between what is felt to be authentic and the facts provided by external sources. Even a cursory glance at the news headlines and social media postings that saturate daily life with terms such as “fake news” and “alternative facts” reveals that this is not an isolated struggle. Focusing on the ways in which contemporary Canadian divination practitioners establish their own truth, this paper examines how these processes reflect and support folklore’s engagement with and ongoing relationship to the emergence of multiple authenticities defined by the experiential.